The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3389/fphar.2018.00244
|View full text |Cite
|
Sign up to set email alerts
|

Diverged Effects of Piperine on Testicular Development: Stimulating Leydig Cell Development but Inhibiting Spermatogenesis in Rats

Abstract: Background: Piperine is the primary pungent alkaloid isolated from the fruit of black peppercorns. Piperine is used frequently in dietary supplements and traditional medicines. The objective of the present study was to investigate the effects of piperine on the testis development in the pubertal rat.Methods: Piperine (0 or 5 or 10 mg/kg) was gavaged to 35-day-old male Sprague-Dawley rats for 30 days. Serum levels of testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Similar effects of piperine were recently reported for pubertal rats administered with piperine (5 and 10 mg/kg) for 30 days. In the mentioned study, piperine increased testosterone (T) and follicle-stimulating hormone (FSH) levels, number and size of Leydig cells, but negatively affected spermatogenesis [84]. This was partially opposite to the results of the earlier study, which reported only negative effects of piperine to testes, and performed the same treatment of mature male albino rats (administered for 30 days at the same doses of 5 and 10 mg/kg).…”
Section: Negative Aspects Of Piperinementioning
confidence: 59%
See 1 more Smart Citation
“…Similar effects of piperine were recently reported for pubertal rats administered with piperine (5 and 10 mg/kg) for 30 days. In the mentioned study, piperine increased testosterone (T) and follicle-stimulating hormone (FSH) levels, number and size of Leydig cells, but negatively affected spermatogenesis [84]. This was partially opposite to the results of the earlier study, which reported only negative effects of piperine to testes, and performed the same treatment of mature male albino rats (administered for 30 days at the same doses of 5 and 10 mg/kg).…”
Section: Negative Aspects Of Piperinementioning
confidence: 59%
“…It activates transient receptor potential cation channel subfamily V member 1 (TRPV1) receptor, a novel anti-epileptogenic target, indicating the anti-seizure effects [83]. Chen et al [84] recently reported the effects of piperine (5 and 10 mg/kg) on the testis development in the pubertal rat, where piperine increased the ratio of phospho-AKT1 (pAKT1)/AKT1, phospho-AKT2 (pAKT2)/AKT2, and phospho-ERK1/2 (pERK1/2)/ERK1/2 in the testis in rats, showing a stimulating effect to the Leydig cell development.…”
Section: Other Enzymesmentioning
confidence: 99%
“…of piperine did not cause any negative effects on reproductive functions and the male germ cells, spermatogenesis, and epididymis enzymes. However, higher doses caused significant reduction in epididymis enzymatic functions, sialic levels, and development of testis in pubertal rats (Chen et al, 2018; D'cruz & Mathur, 2005; Daware, Mujumdar, & Ghaskadbi, 2000). In an earlier report, researchers observed a partial to severe degeneration of germ cells when albino rats were fed with 5 and 10 mg/kg b.w.…”
Section: Toxicological Insights Of Piperinementioning
confidence: 99%
“…Deng et al ( 26 ) demonstrated that activation of the PI3K/AKT signaling pathway promoted myocardial survival by attenuating ERS-induced apoptosis. Moreover, there is a close relationship between PIP and the activation of the PI3K/AKT pathway ( 13 ). Chen et al ( 13 ) revealed that PIP promoted Leydig cell development but inhibited spermatogenesis in rats by activating AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a close relationship between PIP and the activation of the PI3K/AKT pathway ( 13 ). Chen et al ( 13 ) revealed that PIP promoted Leydig cell development but inhibited spermatogenesis in rats by activating AKT. Consistent with a previous study ( 13 ), the present study validated that pretreatment with PIP not only inhibited apoptosis induced by H/R injury, but also upregulated the expression of p-PI3K and p-AKT.…”
Section: Discussionmentioning
confidence: 99%